UK neonatal intensive care services in 1996. Issue 3 (1st May 1999) - Tucker, Janet; Tarnow-Mordi, William; Gould, Craig; Parry, Gareth; Marlow, Neil
Abstract : A census of activity and staff levels in 1996 was conducted in UK neonatal units and achieved a 100% response from 246 units. Among the 186 neonatal intensive care units, the median (interquartile range) number of total cots was 18(14−22); level 1 intensive care cots 4(2−6); total admissions 318(262−405); very low birthweight admissions 40(28−68); and the number ventilated or given CPAP by endotracheal tube 52(32−83). Forty six (25%) intensive care units lacked the recommended minimum of one consultant with prime responsibility for neonatal medicine. As a conservative estimate 79% of intensive care units had a lower nursing provision than that recommended in previously published guidelines. There was substantial variation in activity and staffing levels among units.